Tradisi Ritual Shinto pada Manga Kamikami Kaeshi Karya Ema Toyama - Wiriani, Ni Made; Ni Kadek Ima Damayanti (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2026)
The focus of this study is the mythology of the gods in the Shinto ritual tradition in Ema Toyama's manga Kamikami Kaeshi. This study aims to describe and analyze: 1) the ritual traditions that appear in the Kamikami Kaeshi comic, and 2) the representation of the mythology of the gods in the Kamikami Kaeshi comic. The method used is descriptive with a qualitative approach. The theories used are from Laurenson and Swingewood regarding Shinto ritual traditions and Peirce's semiotic theory regarding mythology. The results of the analysis show that the representation of Shinto ritual traditions in the form of shikigami, haraigushi, kagura dance, miko, omamori, hokora, torii, mirrors, and swords not only serve as aesthetic elements but also reflect the values, beliefs, and socio-cultural structure of Japanese society. The mythology of gods in the Kamikami Kaeshi manga is depicted through the visualization of gods and goddesses such as Izanami, Sarutahiko, Ninigi, Uzume, Izanami, Amaterasu, and Tsukuyomi, which are consistent with the forms of signifiers. Thus, manga can be understood as an effective medium for transmitting religious and social values through visual narratives rooted in local traditions and mythology.